Functional cancer genomics - Beijersbergen, Roderick (Henry Stewart Talks, 2015)
Cancer Genomics, molecular targeted therapies, RNA interference- Genome editing CRIPSR/CAS9, Pooled screening technology in vitro, Pooled screening technology in vivo, Feedback regulation, Combination Therapies